Post-C-Section Pain Management with the Enhanced Recovery after Surgery and Multimodal Analgesia Methods: A Case Series - Poppy Novita Rini; Charles Wijaya Tan (HM Publisher, 2023)
Introduction: This study aims to present the management of postoperative c-section pain using multimodal analgesia. Case presentation: There were two patients who received multimodal analgesia as a treatment for postoperative C-section pain. The first patient, a woman 15 years old, will undergo a Caesarean section operation with indications G1P0A0, term pregnancy, and cephalopelvic disproportion (CPD). The second patient, a 23-year-old woman, will undergo a Caesarean section operation with indications G1P0A0, term pregnancy, and 1x umbilical cord. Physical examination of both patients showed vital signs within normal limits. Laboratory evaluation within normal limits. Both patients were included in the ASA II category. The anesthetic method used intraoperatively was subarachnoid block with hyperbaric bupivacaine 0.5% 10 mg and morphine 50 mcg. Lidocaine infiltration injection is performed intraoperatively in combination with the following; lidocaine 2% (3 ampoules), dexamethasone 4 mg, ketorolac 60 mg, and morphine 4000 mcg dissolved in aquabides into 20 ml subcutaneously. Conclusion: A multimodal analgesia is an appropriate approach for postoperative pain management in patients undergoing cesarean section.